2016
DOI: 10.1590/0034-737x201663020010
|View full text |Cite
|
Sign up to set email alerts
|

Cantaloupe melon ( Cucumis melo L.) conservation using hydrocooling

Abstract: Maintaining cantaloupe melon at field temperature impairs conservation as it speeds up cell metabolism and transpiration, and, consequently, reduces shelf life. This study aimed to evaluate the conservation of Torreon hybrid cantaloupe using the hydrocooling treatment. Fruits were harvested at the commercial maturity stage (60 days after planting), in the morning, at the Nova California Farm, municipality of Mossoró-RN, in September 2007. One set of fruit was immersed in chilled water at 5 ºC for 5 min, at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The results showed that immersion hydrocooling could exponentially reduce the temperature of the lettuce, and the final internal temperature was stabilized at around 8 °C after 5 min. Similarly, Aroucha et al [ 29 ] found that hydrocooling was effective in maintaining the firmness and soluble solids of cantaloupe fruits and minimizing the precooling time in the forced air circulation tunnel. However, the hydrocooling did not extend cantaloupes shelf life.…”
Section: Discussionmentioning
confidence: 98%
“…The results showed that immersion hydrocooling could exponentially reduce the temperature of the lettuce, and the final internal temperature was stabilized at around 8 °C after 5 min. Similarly, Aroucha et al [ 29 ] found that hydrocooling was effective in maintaining the firmness and soluble solids of cantaloupe fruits and minimizing the precooling time in the forced air circulation tunnel. However, the hydrocooling did not extend cantaloupes shelf life.…”
Section: Discussionmentioning
confidence: 98%
“…A high loss of flesh firmness during storage was also reported by Véras et al (2019) on 'Galia' melons, which had a reduction of 68% and 71% on this parameter when stored at 7°C for 14 days under normal and modified atmosphere, respectively. The reduction of firmness in melons during storage is reported in all studies about their conservation (Aroucha et al, 2016). Melons from cantaloupensis groups commonly have several and intense modifications in texture during ripening, which may result in poor storage capacity and short shelf life (Farcuh et al, 2020).…”
Section: Internal Appearance and Flesh Firmnessmentioning
confidence: 99%
“…Vacuum cooling leads to water loss and is not suitable for products with a low surface-to-volume rate [13,14]. Hydrocooling could reduce water loss, avoid skin softening of crops, and is about 2-15 times faster than forced-air cooling under similar conditions [15,16]. Litchi, apple, cherry, sweet corn, radishes, Barhee dates, and carrots are precooled successfully using hydrocooling [8,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%